Nomenclatural issues in Korean insects. Part 1. Hemiptera - Cho, Geonho; Jung, Sunghoon; Lee, Seunghwan (Zootaxa, 2020)
This work is intended to expose nomenclatural issues and provide partial solutions involving Korean insects of the order Hemiptera. The 16 species described by Cheong (2015) and Yoon et al. (2015) are insufficient in zoological nomenclature. The unavailable name Harpocera josifovi Kim & Jung, sp. nov. is validated. The new replacement name Aphis rhamnus Lee, Lee & Kim, nom. nov., is proposed for Aphis rhamnicola Lee, Lee & Kim, 2015 nec Aphis rhamnicola Mamontova, 1953. These actions will provide fundamental information to avoid potential mistakes and guide future discussions.